Length-Weight Relationship of Longtail Hillstream catfish Olyra longicaudata (McClelland, 1842) - Shrestha, Samjhana; Risal, Anjali; Shrestha, Jay Narayan (Our Nature, 2019)
The present study reports the length weight relationshipof Olyralongicaudata from Chisang River, Nepal. Study was carried out in 30 fishes collected from April 2019 to Jul 2019. The body weight ranged from 0.8 to 5.2 g and total length from 6.1 to 13.4 cm. Regression analysis was done to analyzed the data. The growth performance of length-weight relationship is found to be highly significant (r=0.936). The fish was found to show isometric growth pattern with exponential value (b) equal to 2.5115.